EFEKTIVITAS PENGGUNAAN MEDIA BOOKLET DALAM PENDIDIKAN GIZI TERHADAP PENGETAHUAN DAN PERILAKU IBU BALITA GIZI KURANG DI WILAYAH KERJA PUSKESMAS BANDAR - Sari, Kenara; Elyarianti; Alamsyah, Sanjaya (Akper Kesdam I/Bukit Barisan Padang, 2025)
ABSTRACT Indonesia faces various nutritional problems, one of the nutritional problems in Indonesia is malnutrition, which is still often found in various regions of Indonesia. Malnutrition is generally caused by poverty, natural disasters, massive layoffs, lack of food availability and poor environmental quality. Research Method: Pre Experimental One Group Pre test and Post test Design. The total population is 2,145 and the sample in this study is 96 people, the Independent variable of this research is (knowledge and behavior of mothers of under-nourished toddlers) and the Dependent variable (health promotion about nutrition using booklet media). Research Results: research results obtained an average knowledge before 62.60 and after 70.42. The Wilcoxon test results showed a p value = 0.000 or 0.000 <0.005. So Ha is accepted and Ho is rejected. The research results showed that the average behavior before and after was 70.83 and 78.65. The Wilcoxon test results showed a p value = 0.000 or 0.000 <0.005. So Ha is accepted and Ho is rejected. The results of the research show that there is effectiveness in using booklet media on the knowledge and behavior of mothers of undernourished toddlers. It can be concluded that there is effectiveness in using booklet media in nutrition education on the knowledge and behavior of mothers of malnourished toddlers in the working area of the Bandar Community Health Center. The suggestion for health workers is that knowledge about nutrition can be disseminated either through the media or providing direct counseling, not only to mothers with toddlers but also to teenagers, so that in the future women can give birth to intelligent children who have good nutritional status. Keywords : Malnutrition, Toddlers, Booklet